Supply chain innovations & firm strategy: pathways to manage institutional voids in emerging markets. Case study of manufacturing firms in Uganda - Abwang, Walter (Graduate School of Business (GSB), 2024)
The outbreak of the coronavirus pandemic in 2020 exposed the vulnerability of the global supply chain to external shocks. The impact of this problem was felt more significantly in the global South, where manufacturing is underdeveloped and relies heavily on supplies from the global North. A resilient and sustainable supply chain network is of practical importance in developing a strong manufacturing sector in Uganda's emerging or growing market. However, due to institutional voids, the manufacturing industry has come under pressure, which has impacted manufacturing firms' operational efficiencies. The overarching purpose of this study was to investigate why and how manufacturing firms in Uganda should apply supply chain innovations and firm strategies to ameliorate institutional voids. Extant literature shows limited discourse has focused on how manufacturing firms respond to institutional voids in Sub Sharan Africa. This study sheds light on the identified research gaps, a theoretical gap in prior research in the supply chain discipline. Previous empirical work in the supply chain has relied much on the Resource-Based View of the Firm and Transactional Cost Theories to study institutional voids in emerging markets. Therefore, Institutional Theory is relatively not used to understand this phenomenon. The study used methods used to collect data. Firstly, multiple case studies were used to collect relevant qualitative data about the state of the supply chain and how and why firms use supply chain innovations and strategies to counter institutional voids' impact. An in-depth qualitative interview with 25 participants was conducted via the Zoom platform. Secondly, a survey and a random sampling approach were used to identify research participants from 95 manufacturing firms. Firstly, the findings showed that several institutional voids exist in the Uganda manufacturing industry regarding the product, labour, capital, regulatory and macro spheres across the supply chain. Secondly, manufacturing firms in Uganda respond to these voids by deploying strategies such as accepting or changing the landscape through advocacy, political ties, and trust. In addition, they bring innovations in and around institutional voids, create partnerships, engage in supplier development, and develop robust business models, including last-mile strategies to ensure product availability, despite the poor infrastructure that hinders product delivery to remote areas. Thirdly, several barriers asphyxiate firms from entirely alleviating these gaps, such as access to technology, cultural bottlenecks, skills gap, the energy crisis in the manufacturing sector, political upheavals that threaten capital formation in the sector, cost barriers, low absorptive capacity in the formal and informal sector. Fourthly, the results showed that manufacturing firms' specific supply chain innovations to combat institutional voids included (i) energy reduction initiatives across the supply chain, (ii) redesigning manufacturing systems, and (iii) processes to reduce raw material wastage, energy consumption, and pollutions. The social impact of the supply chain has resulted in improved living conditions for consumers and communities through climate change initiatives such as planting trees to provide alternative energy sources for manufacturing firms. The results show that supply chain innovations exemplified by reduce, reuse, and recycle principles have resulted in some manufacturing firms using coffee husks and waste from other industries, such as brewing by-products, to reduce the over-dependence on furnace oil as an energy source. This study makes a significant original contribution to knowledge, lessening the theoretical, methodological, and contextual gaps identified in the literature. It promotes institutional theory application in the supply chain management discipline. The research adds to the existing literature about institutional voids in emerging markets with particular attention on the supply chain and how supply chain innovations and firm strategy can ameliorate institutional voids. The study's practical implication shows a need to develop scalable supply chain innovations to alleviate the wicked problems in developing markets: poverty, disease, and unemployment, a problem in Uganda. Additional interventions and suggestions are to conduct studies in other East African countries to verify the results from this study and compare how firms in the manufacturing and service industries respond to institutional voids in the developing countries in East Africa. The propositions developed in this study can also be tested across multiple industries in Sub-Saharan African countries to provide scholars with new datasets and insights on how firms respond to institutional voids in the region.